2010
DOI: 10.1124/dmd.109.030601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the CYP2C19*17 Allele on the Pharmacokinetics of Omeprazole and Pantoprazole in Children: Evidence for a Differential Effect

Abstract: ABSTRACT:The impact of the CYP2C19*17 allele on the pharmacokinetics of pantoprazole and omeprazole in previously studied children (n ‫؍‬ 40) was explored. When pantoprazole area under the plasma concentration versus time curve (AUC) was examined as a function of CYP2C19 genotype, a significantly lower AUC was observed for subjects identified as CYP2C19*1/*1 and *1/*17. For pantoprazole, a statistically significant relationship was observed between CYP2C19 genotype and both dose-corrected AUC (p < 0.0001) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…Even in homozygotes, any observed ultrafast metabolic profiles have been within the range seen in the wild-type homozygotes. In addition, other authors have reported (Kearns et al, 2010) that, although for pantoprazole, a statistically significant relationship was observed between CYP2C19*17 and both dosecorrected areas under the curve and the apparent elimination rate constant, no significant genotype-phenotype relationships were observed for omeprazole. Unfortunately, CYP2C19*17 was not initially included in the study, and we cannot contribute to clarify how it influences the observed effects.…”
Section: Discussionmentioning
confidence: 87%
“…Even in homozygotes, any observed ultrafast metabolic profiles have been within the range seen in the wild-type homozygotes. In addition, other authors have reported (Kearns et al, 2010) that, although for pantoprazole, a statistically significant relationship was observed between CYP2C19*17 and both dosecorrected areas under the curve and the apparent elimination rate constant, no significant genotype-phenotype relationships were observed for omeprazole. Unfortunately, CYP2C19*17 was not initially included in the study, and we cannot contribute to clarify how it influences the observed effects.…”
Section: Discussionmentioning
confidence: 87%
“…Some drugmetabolizing enzymes display ontogeny (2,3) in humans, but the ontogeny of drug transporters has been described only in murine models.…”
mentioning
confidence: 99%
“…In the study by Ramsjö et al [38], it was reported that the cut-off in Koreans was as high as -3.04, while it was a low -0.86 17 in a Swedish cohort. The cut-off value separating the PM and IM phenotypes in this study was -1.152, which is within the range of cut-off values previously reported.…”
Section: Phenotypingmentioning
confidence: 99%
“…Plasma concentrations of omeprazole sulphone, a CYP3A4 metabolite, could have been measured to evaluate if this was indeed the case, but this was not within the scope of the project. Kearns et al [17] highlight this dilemma and suggest pantoprazole (also a proton pump inhibitor) as a more selective probe drug for CYP2C19 phenotypic analysis. Metabolism of escitalopram, an antidepressant and selective serotonin reuptake inhibitor, has also been shown to not be influenced by CYP2C19*17, and is hence another example of where metabolism predictions may be substrate specific [16].…”
Section: Cyp2c19 Comparison Between Predicted and Measured Phenotypementioning
confidence: 99%
See 1 more Smart Citation